Introduction: Archaeology of African Diaspora Contexts in Brazil. (3rd May 2016) - Symanski, Luís Cláudio P.
Abstract : Archaeological studies of African diasporic contexts in Brazil have expanded significantly in the last 15 years. While earlier studies in the 1980s and 1990s focused on maroon settlements, a wider diversity of contexts have been studied in the last 15 years. This broad spectrum of subjects includes plantations' slave quarters, urban spaces, cemeteries, religious houses, and contemporary maroon settlements. This introduction presents an overview of these recent developments and of earlier studies to better locate the contributions of the articles in this thematic collection within this expanding field of research.